UPAYA HUKUM DALAM PENYELESAIAN SENGKETA PERDAGANGAN EMAS BERJANGKA PADA PT. RIFAN FINANCINDO BERJANGKA PEKANBARU - Andi Aswandi (STIH Putri Maharaja, 2019)
Gold futures trading is very vulnerable to disputes. Therefore, understanding the efforts to resolve futures trade disputes is very important to know. This research was conducted empirically, the nature of descriptive analysis research with qualitative data analysis. Futures trading dispute at PT. Rifan Financindo Berjangka Pekanbaru is caused by customer misunderstanding about the process and legal aspects of futures trading. This was made worse by the lack of education conducted by futures brokers and the existence of unlawful acts committed by sales marketing and futures broker representatives. Gold futures trade dispute settlement can only be done by litigation in the South Jakarta District Court or non-litigation through the Commodity Futures Trading Arbitration Board. Constraints encountered in resolving disputes are; disproportionate choice of dispute resolution forums, lack of customer understanding of legal aspects in resolving disputes and violations of Standard Dispute Resolution Operational Procedures.